Non-Linear Load Control for Grid-Connected Single-Phase Inverters with Voltage Regulation (International Journal of Food and Nutritional Sciences, 2021)
This study focuses on the advancement of sustainable energy sources. This project aims to provide a functional simulation model of a solar panel with SIMULINK within the MATLAB environment. The primary aim is to integrate renewable energy principles and control systems to enhance the quality and quantity of power produced from solar and wind sources. The electricity derived from solar and wind energy sources typically operates within a specific range. However, the integration of solar and wind energy sources, together with the use of power electronic converters, is expected to result in increased quantity and enhanced efficiency of the generated electricity. By integrating the generated electricity with a smart grid system, both the customer and the producer will benefit and experience satisfaction. Keywords: PV System, Boost converter, Inverter, Filter, Grid synchronization, non-linear loads